Coupled Fixed Point Theorems for Two Maps in Complex Valued \(G_b\)-Metric Spaces - Kumar, Jitender; Vashistha, Sachin (Research and Applications Towards Mathematics and Computer Science Vol. 1, 2023)
In this study, we define coupled fixed point for a mapping in complex valued Gb metric space, prove a few coupled fixed point theorems in this space, and give an illustration to illustrate our main theorem. Fixed point theory has great importance in science and mathematics. Since this area has been developed very fast over the past two decades due to huge applications in various fields such as nonlinear analysis, topology and engineering problems, it has attracted considerable attention from researchers. In this paper, we proved a coupled fixed point theorem in complex valued Gb-metric space which genealized the result of Kumar and Vashistha [1] and many others.